Differences in Student Learning Outcomes in Islamic Cultural History Lesson Using TPR Cooperative Learning Model with STAD Type - Zebua, Syafrudin; Arsyad, Junaidi; Nahar, Syamsu (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this study is to see if there are any differences in student learning outcomes when using the Think Pair Share (TPS) cooperative learning model with the Student Teams Achievement Division (STAD) type in Islamic Cultural History Subject with Umayyad Bani material in class VII MTs. Gunung Sitoli City State, Academic Year 2020/2021 This is an example of experimental research. The research population consisted of all VIIMTs students. The population of Gunung Sitoli City was 51 students, and the sample size was 51 people. A test is a tool used to collect data. According to the data analysis, the average pre-test value for the experimental class was 56.48, with a standard deviation (SD1) of 10.09, and the average pre-test value for the control class was 45.23, with an SD2 of 7.57. The average post-test value for the experimental class () is 86.36, with a standard deviation (SD1) of 7.97, while the control class's average post-test value is 78.46, with a standard deviation (SD2) of 6.60. The normality test revealed that Lo>Ltable and the homogeneity test revealed that Ftable>Fcount. The two-party t-test was used to test the research hypothesis, and the results were tcount = 2.401 and ttable = 1.677 at a significance level of 0.05, indicating that tcount > ttable. As a result, it is possible to conclude that there is a positive and significant difference in student learning outcomes in grade VII MTs when using the TPS type cooperative learning model versus the STAD type. Gunung Sitoli City's State in Islamic Culture Subjects with Umayyad Material for the 2020/2021 Academic Year.